ANXIETY OF THE MAIN CHARACTER IN THE NOVEL DO NO HARM - Kusuma, Andre Fahrezi; Hariningsih, Agnes Setyowati; Suharyati, Henny (Universitas Pakuan, 2024)
This study discusses the anxiety that comes from the trauma experienced by the main character. The novel Do No Harm by Christina McDonald is taken as the research corpus which was written in 2021. The descriptive analysis method is applied in this research. The objective of this research is to show that anxiety has a major impact on the behavior of the main character. The research findings posit that the main character's anxiety begins when her son, Josh is diagnosed with cancer. This anxiety makes the main character take various actions to solve the problem, but all her actions have a negative impact on herself and others. The content provided is an excerpt from a novel titled